Anticipating policy considerations for a future HIV vaccine: a preliminary study. Issue 32 (12th July 2016) - Williams, Emmanuel Ato; Lewis, David J.M.; Bertholet, Sylvie; Zazzi, Maurizio
Abstract: Background: New human immunodeficiency virus (HIV) infections continue to occur worldwide. Despite previous failures, there is renewed optimism about developing an efficacious HIV prophylactic vaccine following the 31.2% vaccine efficacy (modified intention to treat analysis) achieved in the RV-144 trial. Intense efforts at characterising the immune responses in the trial participants who appeared to gain some protection from the candidate vaccine are ongoing to delineate correlates of protection. However, the characteristics of a vaccine suitable for programmatic introduction in high prevalence areas remain undefined. Aims: We set out to ascertain the vaccination policies and strategies that policy makers involved in vaccine introductions would advise were a candidate HIV vaccine to become available. Methods: Structured questionnaires in both English and French were self-administered to consenting policy makers such as members of National Immunisation Technical Advisory Groups. Members from three out of the six WHO regional groups were purposively reached for their responses. Results: Thirty-seven key opinion leaders were approached through self-administered questionnaires delivered by e-mail or in person. Nine responses were received, representing a 24.3% response rate. The responses received were from three [Africa (6), Americas (1) and Europe (2)] out of the six WHO regions. All respondents would prioritise the vaccination of commercial sex workers over other risk groups if there was an efficacious HIV vaccine. Vaccine efficacy was considered to be the most important factor, ahead of vaccine safety and cost, in determining the acceptability of a new prophylactic HIV vaccine. Conclusions: It is expected that the first generation HIV vaccines may be modestly efficacious. However, even a modestly efficacious vaccine might curtail the spread of HIV if universal or near-universal coverage is achieved. It is important to anticipate policy discussions which would influence how rapidly an HIV vaccine would be rolled-out programmatically to achieve maximum impact.